Maternal education, home environments and the development of children and adolescents - Pedro Carneiro; Costas Meghir; Matthias Parey (Centre for Microdata Methods and Practice (cemmap), 2010)
We study the intergenerational effects of maternal education on children's cognitive achievement, behavioral problems, grade repetition and obesity. We address the endogeneity of maternal schooling by instrumenting it with variation in schooling costs during the mother's adolescence. Using matched data from the female participants of the National Longitudinal Survey of Youth 1979 (NLSY79) and their children, we can control for mother's ability and family background factors. Our results show substantial intergenerational returns to education. For children aged 7-8, for example, our IV results indicate that an additional year of mother's schooling increases the child's performance on a standardized math test by almost 0.1 of a standard deviation, and reduces the incidence of behavioral problems. Our data set allows us to study a large array of channels which may transmit the effect of maternal education to the child, including family environment and parental investments at different ages of the child. We find that income effects, delayed childbearing, and assortative mating are likely to be important, and we show that maternal education leads to substantial differences in maternal labor supply. We investigate heterogeneity in returns, and we present results focusing both on very early stages in the child's life as well as adolescent outcomes. We discuss potential problems of weak instruments, and our results are found to be robust to changes in our specification. We discuss policy implications and relate our findings to the literature on intergenerational mobility.
Keywords: 330; Bildungsniveau; Eltern; Bildungsverhalten; Sozialisation; Kinder; Schätzung; Großbritannien